Dinuclear neodymium and lanthanum bis(2, 6‐diisopropylphenyl) phosphate complexes bearing a hydroxide ligand: catalytic activity of the Nd complex in 1, 3‐diene polymerization. Issue 6 (11th May 2018) - Minyaev, Mikhail E.; Korchagina, Sof'ya A.; Tavtorkin, Alexander N.; Churakov, Andrei V.; Nifant'ev, Ilya E.
Abstract : Crystal structures of the [La2 {(2, 6‐ i Pr2 C6 H3 ‐O)2 POO}5 (OH)(H2 O)2 ]·2(hexane) and [Nd2 {(2, 6‐ i Pr2 C6 H3 ‐O)2 POO}4 (OH)(H2 O)4 ] + [(2, 6‐ i Pr2 C6 H3 ‐O)2 POO] − ·2(heptane) complexes bearing both bis(2, 6‐diisopropylphenyl) phosphate and hydroxide ligands exhibit intra‐ (La) or intermolecular (Nd) O—H…O hydrogen bonds. The neodymium complex demonstrates catalytic activity in 1, 3‐diene polymerization. Abstract : The reactions of K[(2, 6‐ i Pr2 C6 H3 ‐O)2 POO] either with LaCl3 (H2 O)7 or with Nd(NO3 )3 (H2 O)6 in a 3:1 molar ratio, followed by vacuum drying and recrystallization from alkanes, have led to the formation of diaquapentakis[bis(2, 6‐diisopropylphenyl) phosphato]‐μ‐hydroxido‐dilanthanum hexane disolvate, [La2 (C24 H34 O4 P)5 (OH)(H2 O)2 ]·2C6 H14, (1 )·2(hexane), and tetraaquatetrakis[bis(2, 6‐diisopropylphenyl) phosphato]‐μ‐hydroxido‐dineodymium bis(2, 6‐diisopropylphenyl) phosphate heptane disolvate, [Nd2 (C24 H34 O4 P)4 (OH)(H2 O)4 ]·2C6 H14, (2 )·2(heptane). The compounds crystalize in the P 21 / n and P space groups, respectively. The diaryl‐substituted organophosphate ligand exhibits three different coordination modes, viz. κ 2 O, O ′‐terminal [in (1 ) and (2 )], κ O ‐terminal [in (1 )] and μ2 ‐κ 1 O :κ 1 O ′‐bridging [in (1 ) and (2 )]. Binuclear structures (1 ) and (2 ) are similar and have the same unique Ln2 (μ‐OH)(μ‐OPO)2 core. The structure of (2 ) consists of an [Nd2 {(2, 6‐ i Pr2 C6 H3 ‐O)2 POO}4 (OH)(H2 O)4 ] + cation and a [(2, 6‐ i Pr2 C6 H3 ‐O)2 POO] − anion, which are bound via four intermolecular O—H…O hydrogen bonds. The molecular structure of (1 ) displays two O—H…O hydrogen bonds between OH/H2 O ligands and a κ 1 O ‐terminal organophosphate ligand, which resembles, to some extent, the `free' [(2, 6‐ i Pr2 C6 H3 ‐O)2 POO] − anion in (2 ). NMR studies have shown that the formation of (1 ) undoubtedly occurs due to intramolecular hydrolysis during vacuum drying of the aqueous La tris(phosphate) complex. Catalytic experiments have demonstrated that the presence of the coordinated hydroxide anion and water molecules in precatalyst (2 ) substantially lowered the catalytic activity of the system prepared from (2 ) in butadiene and isoprene polymerization compared to the catalytic system based on the neodymium tris[bis(2, 6‐diisopropylphenyl) phosphate] complex, which contains neither OH nor H2 O ligands.